KARAKTERISTIK FISIK TANAH DI LAHAN PERKEBUNAN KELAPA SAWIT (Elaeis guineensisn Jacq) KEBUN LONSUM - Efendi, Julpan; Matondang, Rassid Dwi Agustian; Saragih, Surya; Daulay, Darul Arif; Saragih, M. Alfiki Hazuan (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
This study was conducted at a plantation in PT. PP. London Sumatra Indonesia Tbk (Lonsum) in Tanjung Morawa, North Sumatra, to determine its suitability for optimal oil palm growth. The main parameters analyzed included total pore space, specific gravity, particle specific gravity, soil texture, pH, and soil water content at two depths (0-20 cm and 0-40 cm). Findings showed good porosity, allowing adequate air circulation and water retention. The surface soil (0-20 cm) was relatively loose with a specific gravity of 38%, becoming slightly denser at 0-40 cm (42%), but still within the acceptable range. The particle specific gravity indicated higher organic matter content in the topsoil. Soil texture changed from sandy loam (0-20 cm) to loamy sand (0-40 cm), providing a balanced environment for root development, drainage, and nutrient retention. Consistent acidic pH (4.2–5.9) was observed at both depths, indicating stable conditions. Soil water content increased with depth, indicating better water retention in deeper layers. Overall, the physical properties of the soil in Lonsum support healthy and productive oil palm cultivation, underscoring the importance of detailed soil analysis for sustainable management practices.